Rakto apsikeitimo protokolas begalinės pusgrupės įvaizdžio lygmenyje - Katvickis, Artūras; Sakalauskas, Eligijus; Ratkevičius, Kastytis (Lietuvos matematikos rinkinys, 2007)
Matrix decomposition problem over integer ring is presented. Solving methods are discussed and it is showed, that this problem is hard computational problem regard to computer memory resources. A key agreement protocol based on matrix decomposition problem is presented.